Class II Human Leukocyte Antigen Variants Associate With Risk of Pegaspargase Hypersensitivity. Issue 3 (21st April 2021) - Liu, Yiwei; Yang, Wenjian; Smith, Colton A.; Cheng, Cheng; Karol, Seth E.; Larsen, Eric C.; Winick, Naomi; Carroll, William L.; Loh, Mignon L.; Raetz, Elizabeth A.; Hunger, Stephen P.; Winter, Stuart S.; et al.
Abstract : We conducted the first human leukocyte antigen (HLA) allele and genome‐wide association study to identify loci associated with hypersensitivity reactions exclusively to the PEGylated preparation of asparaginase (pegaspargase) in racially diverse cohorts of pediatric leukemia patients: St Jude Children's Research Hospital's Total XVI (TXVI, n  = 598) and Children's Oncology Group AALL0232 ( n  = 2, 472) and AALL0434 ( n  = 1, 189). Germline DNA was genotyped using arrays. Genetic variants not genotyped directly were imputed. HLA alleles were imputed using SNP2HLA or inferred using BWAkit. Analyses between genetic variants and hypersensitivity were performed in each cohort first using cohort‐specific covariates and then combined using meta‐analyses. Nongenetic risk factors included fewer intrathecal injections ( P  = 2.7 × 10 −5 in TXVI) and male sex ( P  = 0.025 in AALL0232). HLA alleles DQB1*02:02, DRB1*07:01, and DQA1*02:01 had the strongest associations with pegaspargase hypersensitivity ( P  < 5.0 × 10 −5 ) in patients with primarily European ancestry (EA), with the three alleles associating in a single haplotype. The top allele HLA‐DQB1*02:02 was tagged by HLA‐DQB1 rs1694129 in EAs ( r 2  = 0.96) and less so in non‐EAs. All single nucleotide polymorphisms associated with pegaspargase hypersensitivity reaching genome‐wide significance in EAs were in class II HLA loci, and were partially replicated in non‐EAs, as is true for other HLA associations. The rs9958628 variant, in ARHGAP28 (previously linked to immune response in children) had the strongest genetic association ( P  = 8.9 × 10 −9 ) in non‐EAs. The HLA‐DQB1*02:02 ‐ DRB1*07:01 ‐ DQA1*02:01 associated with hypersensitivity reactions to pegaspargase is the same haplotype associated with reactions to non‐PEGylated asparaginase, even though the antigens differ between the two preparations.